Pengaruh Model Group Investigation Berorientasi Socioscientific Issues terhadap Kemampuan Berpikir Kritis dan Pemecahan Masalah pada Materi Sistem Pencernaan Manusia - Nur Fauziah Salsabila; Aditya Pratama Rizky (Lembaga Publikasi Ilmiah Nusantara, 2026)
Critical thinking and problem-solving are essential twenty-first-century competencies that remain insufficiently developed through conventional instructional approaches, particularly in learning the human digestive system. This study aimed to examine the effect of the Group Investigation (GI) learning model oriented toward Socioscientific Issues (SSI) on senior high school students' critical thinking and problem-solving skills in the human digestive system topic, analyze differences in learning improvement between the experimental and control groups, and evaluate the effectiveness of the model based on the N-Gain index. The study was conducted at a public senior high school in Pekanbaru using a quasi-experimental pretest-posttest control group design. A total of 62 eleventh-grade science students participated as research subjects. Data were collected using validated critical thinking and problem-solving tests. The results revealed that the experimental group achieved higher posttest mean scores in critical thinking (74.06%) and problem-solving (72.20%) than the control group (61.42% and 59.07%, respectively). The N-Gain values of the experimental group were classified as moderate (0.57 and 0.55), whereas those of the control group were categorized as low (0.34 and 0.33). An independent samples t-test confirmed that the differences between the two groups were statistically significant (p < 0.001). These findings demonstrate that the SSI-oriented Group Investigation model is more effective than conventional instruction in improving students' critical thinking and problem-solving skills.